PEMBERHENTIAN TIDAK DENGAN HORMAT APARATUR SIPIL NEGARA DALAM KASUS TINDAK PIDANA KORUPSI - Erawan, Dhani I Ihza; Ilmar, Aminuddin; Mirzana, Hijrah Adhyanti (Universitas Gorontalo, 2024)
This study aims to analyze the dishonorable dismissal of state civil servants in corruption cases. This type of research is the type of research used is normative juridical research. The approach used is) in this study, namely the statutory approach (statute approach), case approach (case approach), and conceptual approach (conceptual approach). The results of this study are based on the original intent of the former of Law no. 43/1999, the Government's interpretation, and the interpretation of the legal norms of PTDH civil servants who committed criminal acts of office before the entry into force of the ASN Law, the enforcement of administrative sanctions does not have to be dishonorably dismissed as civil servants, but becomes the discretion of the PPK. PPK assesses and considers whether to be dishonorably discharged, honorably discharged not at his own request, or not dismissed with or without imposition of disciplinary punishment by taking into account the factors that encourage civil servants to do this and paying attention to the severity of the criminal sentence imposed. SKB 3 of the Minister is a policy regulation issued as an implementation guideline for PPK which regulates the honorable or dishonorable dismissal of civil servants who commit criminal acts of office crimes or crimes related to their positions based on court decisions that have permanent legal force. Second, the SKB 3 Ministers can be qualified as a legal juridical instrument (rechtmatig), unless it is enforced backwards (terugwerkend).